Proceedings of the 2015 ACM SIGMIS Conference on Computers and People Research 2015
DOI: 10.1145/2751957.2751978
|View full text |Cite
|
Sign up to set email alerts
|

Insider Threat

Abstract: Language as a symbolic medium plays an important role in virtual communications. Words communicated online as action cues can provide indications of an actor's behavioral intent. This paper describes an ongoing investigation into the impact of a deceptive insider on group dynamics in virtual teamcollaboration. An experiment using an online game environment was conducted in 2014. Our findings support the hypothesis that language-action cues of group interactions will change significantly after an insider has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Ho, Hancock et al's [37,38] findings are consistent with Taylor, Dando et al's [68] findings, suggesting that, in both asynchronous and synchronous communication, deceptive leaders can be expected to use more words associated with cognitive processes in their communication than other members from the same group. In a different set of hypotheses, Ho, Hancock et al [40] further identified differences in language-action cues-not only between deceptive leaders and non-deceptive leaders-but also between groups with a deceptive leader and groups without one.…”
Section: Cognitive Processmentioning
confidence: 53%
See 1 more Smart Citation
“…Ho, Hancock et al's [37,38] findings are consistent with Taylor, Dando et al's [68] findings, suggesting that, in both asynchronous and synchronous communication, deceptive leaders can be expected to use more words associated with cognitive processes in their communication than other members from the same group. In a different set of hypotheses, Ho, Hancock et al [40] further identified differences in language-action cues-not only between deceptive leaders and non-deceptive leaders-but also between groups with a deceptive leader and groups without one.…”
Section: Cognitive Processmentioning
confidence: 53%
“…As the most prominent insider threat cases are often committed by those who are in power positions and betray inherent trust [37,38], we note that certain influences can be found in the deceptive leader's exchange with the subordinates, and further impact the subordinates commitment to the organization [31]. Griffith, Connelly et al [31] validated the deceptive leader's influences on leader-member exchange using survey instruments, while Ho, Hancock et al [37,38] simulated experiments to investigate the differences in language-action cues between deceptive leaders and non-deceptive leaders in group interaction, and specifically how language-action cues from groups that include a deceptive leader differed from those of groups that did not include a deceptive leader.…”
Section: Cognitive Processmentioning
confidence: 99%
“…Identification of deception is a complex problem that often requires ground truth verification [11,15]; nevertheless, deception can be detected in interpersonal communication [1,[21][22][23] as well as group communication [24,25]. Research into CMC deception cues has examined a variety of media types and modes of communication, while also exploring the role of media choice and mode of communication.…”
Section: Environmentmentioning
confidence: 99%
“…Ho, Hancock et al [25], [24] examined behaviors of a deceptive "insider" in spontaneous synchronous chat-based group-dynamics context, and suggested that deceptive "insiders" in computer-mediated synchronous interactions will tend to use more words associated with cognitive processes. Ho, Hancock et al's [25] findings are consistent with those of Taylor, Dando et al [35], and suggest that deceptive "insiders" tend to use words more associated with cognitive processes in their communication with their peers in either asynchronous or synchronous communication.…”
Section: Group Communicationmentioning
confidence: 99%